The Effect of Early Breastfeeding Initiation on Newborn Body Temperature Changes at RSUD.I.A Moeis Samarinda in 2022 - Yuliana; Jasmawati; Rivan Firdaus (Formosa Journal of Science and Technology, 2022)
Initiation of Early Breastfeeding and Exclusive Breastfeeding during the first 6 months of life prevents around 20% of newborn deaths and 13% of under five deaths. It can also reduce deaths from neonatal infections (sepsis pneumonia, tetanus and diarrhea) which contribute 36% to neonatal deaths. Early breastfeeding initiation (IMD) in South Asia remains low to varying degrees. The purpose of this study was to find out whether there is an effect of IMD on changes in the body temperature of newborns at RSUD.I.A.Moeis in 2022. The design in this study was quasi-experimental with a number of samples. The number of samples in this study were 17 infants with a purposive sampling technique. The paired samples t-test statistic obtained a value of t = -11.6 and p = 0.001 (p <0.05) meaning that there was a significant effect of implementing IMD on increasing the body temperature of newborns (BBL). From the results of the study it can be concluded that there are differences in the body temperature of newborns who have successfully performed IMD and those who have not successfully performed IMD.